Dulcan's textbook of child and adolescent psychiatry - Dulcan, Mina K. (American Psychiatric Association Publishing, 2016)
This thoroughly updated and more compact edition is designed to be used as a core textbook for child and adolescent psychiatry fellowship training as well as a reference for practicing child and adolescent psychiatrists, pediatricians, family physicians, advanced practice nurses, psychologists, psychiatric social workers, and others.